Optimal entropy generation in Darcy-Forchheimer magnetized flow in a square enclosure filled with silver based water nanoliquid - Fares, R.; Mebarek-Oudina, Fateh; Aissa, A.; Bilal, S. M.; Öztop, Hakan Fehmi (Springer, 2022)
Current communication candidly explicates the incremental aspect of generated entropy in apermeablesquare enclosure. Porosity aspects are mathematically formulated by Darcy-Forchheimer model, whereas the Lorentz force law is manifested to enclose magnetic field effectiveness. Water is capitalized as base fluid and nanoparticles composed of silver with different nanoparticles volume fractions are obliged. Thermal buoyancy is generated within the flow domain by provision of heat to left boundary. Description about physical modeling of the problem is manipulated in the form of PDEs with boundary constraints. Finite element procedure is used as a solution procedure to sort out the characteristics of flow problem. Variation in thermophysical attributes is presented through stream patterns, isothermal plots against flow contributing variables. Convective heat transfer through boundaries is measured through Nusselt number calculations.
Keywords: Free convection; MHD; Entropy generation; Porous cavity; Nanofluid